KEEFEKTIVAN PROGRAM GENERASI BERENCANA (GenRe) KOTA SURAKARTA DALAM PENGUATAN CIVIC RESPONSIBILITY - Triyanto Triyanto; Alifi Kurnia Dzulhijjah (Prodi PPkn Universitas Slamet Riyadi, 2020)
The purpose of this research is to find out the effectiveness of the Surakarta City GenRe Program in strengthening civic responsibility. The research method used in qualitative research with a case study method. GenRe Program is able to be a good forum for the formation of adolescent characters, especially in strengthening civic responsibility. This success can certainly be achieved by various factors. As for one of the factors that influence that is related to strategy. Some of the strategies needed are (1) Maximizing SDM by managing GenRe Program services; (2) Establishing and developing PIK R in several regions; (3) Developing the GenRe Program; (4) Increasing the GenRe program partnership; (5) Develop coaching and evaluation periodically. Thus the GenRe program is able to produce teenagers who can be educated consistently and in accordance with their capacities through maximizing their potential while forming civic responsibility Keywords: GenRe Program, Raising Potential for Youth